Anaphylaxis viewed by experts: unmet needs. Issue 5 (15th October 2021) - Sala-Cunill, Anna; Cardona, Victoria
Abstract : Purpose of review: The purpose of the review is to identify unmet needs in the management of anaphylaxis, covering aspects such as epidemiology, diagnosis, treatment and prevention. Recent findings: Redefinition of clinical diagnostic criteria may allow a better identification of anaphylaxis. International diagnostic coding system improvement will be major step for future policies and epidemiological studies. Digital health can aid in managing anaphylaxis. Summary: Anaphylaxis is a medical emergency; current data show that frequently identification of the reaction, acute and long-term management, are not optimal. Therefore, there is a need to implement strategies to improve the situation. This review has identified unmet needs in anaphylaxis regarding aspects such as epidemiology, severity scoring, definition and diagnostic criteria, anaphylaxis in infants and toddlers, cofactors, biomarkers, long-term management, undertreatment and availability of epinephrine autoinjectors. Strategies focused on education, legislation, digital health and research are proposed.